PRACTICE CLASSES AS FACILITATING METHODOLOGY OF LEARNING PROCESS AT PHYSIC IN SCIENCE COURSE - Rodrigues Lopes , Márcia; das Graças Nascimento Amorim, Adriany (Journal of Interdisciplinary Debates, 2021)
Experimental activities as a facilitating agent in the teaching-learning process have been increasing presence in the science course. Therefore, this work aimed to show the importance of practice activities involving physics subjects such as mechanics and electrostatics in science courses. The main problems confronted by students are related to the types of methodological procedures, the lack of adequate knowledge in the introduction of the teaching of physics, the lack of professionals trained in the area, and focusing on only mathematical foundation and formulas memorization teaching. Because of this, classes aimlessly create fragmented insight concerning the science course. Enhance the importance of teaching physics and simultaneously defend the use of low-cost materials in experimental activities stimulate the student a thirst for knowledge and enhances the teaching-learning process in science. Thus, urging students' interest in materials handling and apply contextualization facilitates and improves knowledge construction, especially in understanding natural sciences contents.